Some we remember, some we forget: The collective memory of assassinated U.S. Presidents in the modern age - Claxton, Haley (Kansas State University. K-State Libraries, 2015)
"Some We Remember, Some We Forget" is a historical study of the modern cultural memory of the four assassinated US presidents, Abraham Lincoln, James Garfield, William McKinley, and John F. Kennedy. The study first provides narrative accounts of each president's assassination, aftermath of the event, and the lasting cultural impact from a modern perspective. Key points include differences between the memorialization of Lincoln and Kennedy and the relative lack of memorialization of Garfield and McKinley. These accounts are followed by analytical sections regarding the current awareness and collective memory of each president's death, offering arguments as to why the amount of awareness between Lincoln and Kennedy's deaths and Garfield and McKinley's is so stark. The first section "Material Remnants" examines physically lasting reminders of each president,. The second section, "Non Material Remnants," is broken up in subsections. The first, "Sudden Shocks and Interminable Infections," concludes that because Lincoln and Kennedy died almost immediately after being shot, their deaths had a greater sociological impact on the American public, than Garfield's and McKinley's delayed deaths, which allowed for more adequate preparation. Subsection two, Presidential Performance and Assassin Appeal," argues that the policies and surrounding events of the Lincoln and Kennedy presidencies had more lasting impact on the American public and that the personal characteristics of the assassins played a role in how each assassination is recalled. The third subsection, "Ritual Rites and Martyred Men," compares the funeral ceremonies and language used in remembrance of each assassinated president, concluding that Lincoln and Kennedy's funerals more publicly available, and that post-mortem orations and writings regarding these two painted them as martyrs, a well-regarded archetype in cultural memory. The final subsection, "Conspiracy and Closure," argues that Kennedy's assassination in particular left Americans with a lack of conclusions leading to a lasting desire to find answers.
Citation: Claxton, H. (2015). Some we remember, some we forget: The collective memory of assassinated U.S. Presidents in the modern age. Unpublished manuscript, Kansas State University, Manhattan, KS.Kirmser Undergraduate Research Award - Individual Non-Freshman category, grand prize
Keywords: John F. Kennedy; James Garfield; WIlliam McKinleyUS Presidents; Assassination; Memory; Abraham Lincoln